A Correlative Study of Reading Speed and Reading Comprehension of the Second Year Students of SMP Islam Sultan Fattah Salatiga in the Academic Year of 2007/2008 - Inna Naili Izzatul Laila (Register Journal, 2008)
This study is conducted to find out the profile of students’ speed reading skill and the students’ reading comprehension, as well as to prove if there is significant correlation between the students’ skill in reading speed and reading comprehension of students of SMP Islam Sultan Fattah Salatiga in the academic year of 2007/2008. The writer applies random sampling technique to take the sample (40) from the total of population of 81 students. Furthermore, the profile of students’ reading speed skill in the text comprehension is observed through applying reading speed limited by time. From such a test, the writer knows how many words produced by students every minute. The students’ reading comprehension, in addition, can be seen from the result of the answered of questions. The data is analyzed using correlative statistics. From the result, the writer finds that there is no correlation between reading speed and reading comprehension of the students. It is shown from the result r0=0,027 and rt=0,312 in the level of significance 5%. Then, there are many factors that influence reading speed and the comprehension as children weakness of vocabularies and the lack of concentration in reading.Keywords: Reading Speed; Reading Comprehension